Multifunctional SnSe–C composite modified 3D scaffolds to regulate lithium nucleation and fast transport for dendrite-free lithium metal anodes. Issue 38 (22nd September 2021) - Shen, Xiaojie; Zhao, Guangyu; Yu, Xianbo; Huang, Huihuang; Wang, Ming; Zhang, Naiqing
Abstract : The synergistic effect of the Li–Sn alloy and Li2 Se to regulate lithium nucleation and fast transport. Abstract : Undesirable lithium dendrite growth limits the application of lithium metal anodes in high-energy storage batteries. Here, multifunctional SnSe–C composite modified 3D scaffolds are constructed to achieve dendrite-free lithium deposition. During the initial lithiation stage, the porous SnSe–C composite converts into a Li–Sn alloy and Li2 Se by lithium reduction. The lithiophilic Li–Sn alloy exhibits a low nucleation barrier and realizes homogeneous lithium nucleation. The reductive product Li2 Se with a high ionic conductivity facilitates lithium ion transport, which helps realizing the homogeneous lithium ion flux and reducing concentration polarization. Benefitting from the synergistic effect of the Li–Sn alloy and Li2 Se, the Li/SnSe–C anode exhibits an ultralong lifespan over 1100 h with a low overpotential of 18 mV. In full-cell configurations with LiFePO4 cathodes, the Li/SnSe–C anode demonstrates enhanced rate capability and cycle stability with a high-capacity retention of 85% over 750 cycles. This work prepares multifunctional SnSe–C composite modified 3D scaffolds to regulate lithium nucleation and transport, which offers new insights and opportunities for developing dendrite-free lithium metal battery technology.